Synergistic promoting effects of bone morphogenetic protein 12/connective tissue growth factor on functional differentiation of tendon derived stem cells and patellar tendon window defect regeneration. (3rd January 2018) - Xu, Kang; Sun, Yanjun; Kh Al-ani, Mohanad; Wang, Chunli; Sha, Yongqiang; Sung, KL Paul; Dong, Nianguo; Qiu, Xuefeng; Yang, Li
Abstract: Current study investigated bone morphogenetic protein 12 (BMP12) and connective tissue growth factor (CTGF) activate tendon derived stem cells (TDSCs) tenogenic differentiation, and promotion of injured tendon regeneration. TDSCs were transfected with BMP12 and CTGF via recombinant adenovirus (Ad) infection. Gene transfection efficiency, cell viability and cytotoxicity, tenogenic gene expression, collagen I/III synthesis were evaluated in vitro . For the in vivo study, the transfected cells were transplanted into the rat patellar tendon window defect. At weeks 2 and 8 of post-surgery, the repaired tendon tissues were harvested for histological and biomechanical examinations. The transfected TDSCs revealed relatively stable transfection efficiency (80–90%) with active cell viability means while rare cytotoxicity in each group. During days 1 and 5, BMP12 and CTGF transfection caused tenogenic differentiation genes activation in TDSCs: type I/III collagen, tenascin-C, and scleraxis were all up-regulated, whereas osteogenic, adipogenic, and chondrogenic markers were all down-regulated respectively. In addition, BMP12 and CTGF overexpression significantly promote type I/III collagen synthesis. After in vivo transplantation, at 2 and 8 weeks post-surgery, BMP12, CTGF and co-transfection groups showed more integrated tendon tissue structure versus control, meanwhile, the ultimate failure loads and Young's were all higher than control. Remarkably, at 8 weeks post-surgery, the biomechanical properties of co-transfection group was approaching to normal rat patellar tendon, moreover, the ratio of type III/I collagen maintained about 20% in each transfection group, meanwhile, the type I collagen were significantly increased with co-transfection treatment. In conclusion, BMP12 and CTGF transfection stimulate tenogenic differentiation of TDSCs. The synergistic effects of simultaneous transfection of both may significantly promoted rat patellar tendon window defect regeneration.